A 6-year-old with childhood absence epilepsy and motor hyperactivity - Stéphane Auvin (Epilepsy & Behavior Reports, 2024)
A case study of a child with childhood absence epilepsy and hyperactivity introduces the discussion around the psychiatric diagnosis, differential considerations, and pharmacologic treatment options for ADHD/hyperactivity in children with epilepsy. Most of the time, ADHD in children with epilepsy is an inattentive form.The assessment emphasizes the need to differentiate ADHD symptoms from other psychiatric comorbidities. This is also crucial to evaluate when symptoms emerged, their impact on daily life, and if it could be a potential medication side effect. Speaking about hyperactivity signs, differential diagnoses include anxiety disorders, autism spectrum disorders, learning disabilities, and thyroid disorders. Valproate use is associated with an exacerbation of attentional issues in childhood absence epilepsy, but there are also studies suggesting its possible role in hyperactivity symptoms.Regarding pharmacologic treatment, limited studies exist on ADHD management in children with epilepsy. Methylphenidate shows effectiveness without significant risk of epilepsy worsening. Atomoxetine and clonidine, usually use in ADHD, lack sufficient data for efficacy and safety in children with epilepsy and ADHD. Pharmacologic treatment should be a part of a global management plan that involves psychoeducation, environmental adaptations, and collaborative efforts between healthcare providers, caregivers, and schools.